Interdisciplinary treatment of ankylosed upper central incisors with an anterior vertical ridge defect: A case report. Issue 1 (27th September 2022) - Madureira, Davidson Frois; Valentim, Gustavo Laignier Lage; da Silva, Tarcília Aparecida; Júnior, Aécio Abner Campos
Abstract: This case report describes the successful 10‐years interdisciplinary treatment of ankylosed upper central incisors with an anterior vertical ridge defect. This treatment was challenging as ankylosis was present before the growth spurt. Orthodontic treatment in association with decoronation, a xenogeneic bone graft, an autogenous sub‐epithelial connective tissue graft, and implant placement were performed to correct the vertical ridge defect and to re‐establish appropriate function, gingival health, and aesthetics. Decoronation performed during the growth spurt was the key to avoiding alveolar ridge deformity.